Disentangling interstellar plasma screens with pulsar VLBI: combining auto- and cross-correlations. Issue 4 (27th July 2019) - Simard, D; Pen, U-L; Marthi, V R; Brisken, W
Abstract: Current methods of measuring distances to pulsar scattering screens rely on a single screen dominating the scintillation pattern. We present a novel technique to reconstruct the scattered flux of a pulsar and solve for the scattering geometry in cases where the scattering environment along the line of sight to the pulsar is complex and may be composed of multiple scattering screens. This technique combines interferometric visibilities with cross-correlations of single-station intensities. It takes advantage of the fact that if one considers the interference of radiation from two points in the scattered image in delay–delay rate space, the visibilities are sensitive to the mean angular position of the points, while the cross-correlated intensities are sensitive to their angular separation. By combining the visibilities and the cross-correlated intensities, it is possible to measure the angular locations of both points in the pair. We show that this technique is able to reconstruct the published scattering geometry of PSR B0834+06. We then apply this technique to one-dimensional simulations of more complicated scattering systems, where we find that it can distinguish features from different scattering screens. This technique holds promise for studies of the interstellar medium and pulsars themselves: It will allow the application of scintillometry techniques, such as resolving pulsar emission regions using interstellar scattering, to sources for which a current lack of understanding of the scattering environment has precluded their use.